Development of evaluative criteria for the pre-service teacher-education programs of the public regional normal schools in the Philippines - San Andres, Maura M. 1926- ([Quezon City s.n.], 1964)
The purpose of this investigation is to develop an evaluative criteria which may be used to assess the pre-service programs for teacher preparation in the regional normal schools in the Philippines.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teachers, Training of -- Philippines